Pelatihan Menulis bagi Peserta Ekstrakurikuler Jurnalistik SMA Negeri 5 Madiun - Wijayanti, Wenny; Adhani, Agnes (Muria Jurnal Layanan Masyarakat, 2023)
The purpose of this community service is to provide experience as well as the ability to write, especially prose fiction, for students of SMA Negeri 5 Madiun. Specifically, students who take part in this community service activity are participants in journalism extracurricular activities. Journalistic extracurricular activities at SMA Negeri 5 are called Student Literacy Studios or Sangrila. This community service produces outcomes in the form of increasing students' ability to make prose fiction frameworks.